Enhancing principals' decision-making through local wisdom and technology in Indonesian elementary schools - Sujatmiko Baliarto; Soewarto Hardhienata; Sri Setyaningsih (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
This study investigates strategies to enhance decision-making effectiveness among public elementary school principals in Bogor, Indonesia. A sequential exploratory mixed-methods design (POP-SDM approach) was employed. Preliminary surveys (n=30) revealed significant gaps in decision-making indicators (targeting accuracy: 58%; timeliness: 53%). Qualitative interviews with 15 principals identified five critical variables: visionary leadership, motekar (Sundanese creativity and initiative), empowerment, trust, and ICT literacy. Quantitative path analysis using PLS-SEM with 138 principals (proportionate random sampling from 209) confirmed that trust exerts the strongest direct effect (β = 0.246, p = 0.002), followed by visionary leadership (β = 0.224) and ICT literacy (β = 0.216). The model explained 51.6% of variance in decision-making effectiveness. SITOREM (Scientific Identification Theory for Operations Research in Educational Management) analysis identified priority indicators for improvement, including consistent development, communication and togetherness, and computer operational skills. This study contributes a novel framework integrating indigenous cultural values with technological competence, offering evidence-based strategies for principal development programs. Limitations include cross-sectional design and geographic specificity; future research should employ longitudinal designs across diverse Indonesian regions.